Movimento de água subterrânea em ecossistema Campina Amazônica () - Reichardt, Klaus; Santos, Antonio dos; Nascimento F, V. F. do; Bacchi, O. O. S. (Acta Amazonica, 1975)
In the period of december 1974 to January 1975 the movement of the ground water in the eco-system of the Campina Amazonica was studied. The saturated flux of the ground water was studied by two methods : 1º) Applying Darcy's equation; 2º) Using a tracer of 3H (100 mCi) in the form of 3H2O. The variations shown by the two methods are derived from a high permeability of the arenaceous soil, proportioning rapid variations in the ground water, totally influenced by precipitation. However the results obtained through applicatios of Darcy's equation and through the method of dilutions are of the same order of magnitude. They indicate the existence of a horizontal movement in the saturated flux of the ground water of Campina, of the same order of 0,0018 cm3. cm-2. h-1. This work is the first attempt to determine the flux magnitude of the underground water, to estimate the potencial elements biologically important in the nutrient cycle, in these formations of Central Amazonian.", 'en